International Arbitration and Energy Disputes. Issue 1 (February 2022) - Cameron, Peter D
Abstract : Arbitration is currently central to the fabric of settling international energy disputes, whether in its commercial or its investment modes. When arbitration is applied to energy disputes, it needs to consider the presence of certain distinct features that can influence the arbitration process. This article identifies and examines eight such features, such as its complexity, scale, duration of projects, their cross-border character, market volatility, strategic concerns, asymmetry, and the pervasive roles of the state. It notes the various efforts at reform of energy arbitration, but argues that such features are likely to strongly influence any regime that evolves from the present one.